The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/0034-7167-2018-0668
|View full text |Cite
|
Sign up to set email alerts
|

Care of the self in the daily living of nurses: an integrative review

Abstract: Objectives: to identify if nurses care for themselves and describe such practices. Methods: this is an integrative review of the literature published between 2006 and 2018 and indexed in the Literatura Latino-Americana e do Caribe em Ciências da Saúde, Medical Literature Analysis and Retrieval System Online and Web of Science databases. Results: the sample totaled 20 articles, grouped by content similarity in the thematic categories “limits and possibilities for the care of the self”, “knowledge about practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
1
0
2
Order By: Relevance
“…11,23 From this perspective, the importance of spirituality is emphasized for self-knowledge, for valuing and caring for oneself in nursing practice. 24 This issue is confirmed by the findings of a study with Chinese nurses, 25 which identified that the religious beliefs of nurses are characterized as an important factor when it comes to the impact on their attitudes about caring for the spiritual dimension.…”
Section: None (Algeria)mentioning
confidence: 82%
“…11,23 From this perspective, the importance of spirituality is emphasized for self-knowledge, for valuing and caring for oneself in nursing practice. 24 This issue is confirmed by the findings of a study with Chinese nurses, 25 which identified that the religious beliefs of nurses are characterized as an important factor when it comes to the impact on their attitudes about caring for the spiritual dimension.…”
Section: None (Algeria)mentioning
confidence: 82%
“…Given that care is the epistemological focus of the nursing profession, nursing plays a strategic role in care management ( 49 ) . To fulfill this role, nursing professionals must integrate care and management actions, prioritizing care based on human needs ( 50 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Por ter o cuidado como objeto epistemológico da profissão, a enfermagem desempenha um papel estratégico na gestão do cuidado (49) . Para exercer esse papel, os profissionais de enfermagem precisam articular ações de cuidado e gestão, priorizando a prestação de cuidados com base nas necessidades humanas (50) .…”
Section: Contribuições Para a áRea Da Enfermagemunclassified